Cleanliness Management as an Effort To Realize SGDs Principles in Penglipuran Tourism Village - WARDHANI, Luh Gede Sintiawati Diah Kusuma; WAHYUNI, Ni Komang Sri; DARMAYANTI, Ni Luh Putu Septi; HERLINAYANTI, Ni Made (PT Batara Swastika Harati, 2025)
Sustainable tourism management in Penglipuran Tourism Village is a strategic step towards achieving the Sustainable Development Goals (SDGs), which highlight the importance of balancing economic growth, environmental protection, and socio-cultural empowerment of local communities. Sustainable tourism management in Penglipuran Village emphasizes cultural and environmental preservation and involves the active participation of village communities in various aspects of tourism. Sustainable tourism management in Penglipuran Village is implemented by emphasizing cultural preservation, environmental protection, and active empowerment of local communities. The village adopts the teachings of Tri Hita Karana, which emphasizes the importance of balance between humans and God, the relationship between humans, and the relationship between humans and nature. This concept serves as the philosophical basis and implementation of tourism management. The community continues to practice traditions and culture in their daily lives without being affected by tourist activities, thus preserving their culture and becoming a major tourist attraction. Tourism village management is carried out systematically, involving local communities as primary managers, who hold responsibility and possess local knowledge to preserve natural and cultural resources. This method ensures the sustainable use of resources and fosters accountability at the local level. Penglipuran Village is an example of successful tourism management that applies sustainability principles by combining cultural preservation, environmental protection, and community empowerment. This provides sustainable social, economic, and cultural benefits for all parties involved.